AN APPRAISAL SYSTEM FOR MONITORING PERFORMANCE OF CONVENIENCE STORES IN TAIWAN - Wu, WY; Bai, CC; Gupta, OK (The South African Journal of Industrial Engineering, 2009)
With service industries achieving almost 70% of GDP, Taiwan has witnessed a major shift in